HEALTHY LIFESTYLES ILLUSTRATION THROUGH DIGITAL BOOK TO PREVENT CARDIOVASCULAR DISEASES - Diny Anggriani Adnas; Jennifer Chandrinova (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2022)
People who live in urban areas that are stills in their productive ages and generally have busy activities often ignore healthy lifestyles and are less aware of its impacts. Due to busyness, people tend to prefer something instant and fast without considering the impacts on their health. Without realizing it triggers the negative impact of a healthy lifestyle. The most dangerous impact is that it can be one of the things that triggers heart disease. Heart disease or cardiovascular is one of the diseases that is quite feared because it can endanger lives. The statement that heart disease only occurs in people aged >50-60 years is now invalid because of the fact that in recent years many young people have suffered from this chronic disease. Problems in big cities in Indonesia have the potential or problems of an unhealthy lifestyle due to an unhealthy lifestyle, and an information media is needed to convey a message about how important a healthy lifestyle is. However, there is still a lot of inaccurate information that is spread on the internet so that it often gives rise to the wrong understanding and mindset for people who read it. Therefore the author wants to design a learning media that can provide accurate information about the importance of a healthy lifestyle. The final result of this research is the design of a media in the form of a digital illustration book about a healthy lifestyle which was created and developed using the four-d method.